Examining shock wave flow past the brim of a helmet using schlieren imaging - Cody Thomas; Catherine E. Johnson (Heliyon, 2025)
Increasing the protection a helmet provides the user from shock waves can help reduce the prevalence of blast induced traumatic brain injury (bTBI). Previous research has shown that air enters and gets trapped in the helmet-head cavity and can increase the overpressure experienced by the wearer. The brim design of the helmet has yet to be studied to understand how shock waves flow into the helmet. By studying a variety of brims, it is possible that the design can be modified to minimize shock wave flow into the helmet. This paper investigated a shock wave impacting interior and exterior facing brims with angles of 20, 30, 45, and 90-degrees, along with a brim with a 45-degree cut. To visualize shock wave flow, 3D printed helmet-head cross-sections were designed and used in a z-style schlieren imagery setup with shock waves created from NONEL lead line. A high-speed camera was used to record each helmet design both with and without helmet pads. Findings reveal that shock wave flow was not impeded due to different brim angles due the shock diffracting around brims and flowing upwards into the helmet cavity. Additionally, the shock wave velocity of the waves flowing upwards was not significantly different, though wave shape changes were observed with the use of different brims. During testing with the helmet pads there was a lack of detectable waves reflecting from the helmet pads after being impacted. This the lack of reflections, indicated shock wave energy was being transmitted through the helmet pads, or shock wave were flowing around the helmet pads. These findings can aid in better informing helmet designers on how shock waves enter the helmet-head cavity.